Harnessing Generative AI for Transformative Innovations in Healthcare Logistics: A Neural Network Framework for Intelligent Sample Management - Karthik Chava (Utilitas Mathematica, 2024)
As healthcare innovations drive an ever-increasing demand for diagnostics or pharmaceutical endeavors, there is a tremendous volume of samples used from patients that require processing through the healthcare supply chain. To achieve accurate diagnostic analyses, embracing an accurate and elaborate sample-management process is fundamental. In addition, by engaging modern frameworks for diagnostic analysis, sample-tracking precision and annotation typing can further facilitate the path to high assay quality. In this study, a brand-new sample-transport framework is suggested that could intelligently circle the sample to entirely visited logistics depots. Moreover, a neural network subtype is developed that accommodates the optimization of sample allocations in respect to both culture, transportation, and processing time, taking into consideration stock conditions. Experimental benchmarks revealed when the sample set expanse was above a particular dimension threshold, the neural network premises significantly enhanced over its benchmark form. The healthcare logistics industry includes countless operations concerning sample and stock-taking management which predispose terminus through diagnostic analyses including routine blood, feces, or urine tests. To assure promising test quality, these samples should be examined within a specific time after sampling and accumulated within a precise stock control environment before laboratory assay. At the same time, samples need to be transported as quickly as possible to ameliorate diagnostic analysis precision and thus medical intervention. However, disregarding an intricate sample-management regulation that controls both the sample traffic pattern for both further depot and the hospital lab, as well as stockistic regulations concerning the sample-transport industry and laboratory constraints, this personalized and accurate process necessitates a ground intensive effort in planning.